Os gêneros textuais na formação do professor de língua portuguesa em instituições de ensino superior - Santos, Hiliana Alves dos (2010)
Although there are innumerable academic productions about genres and a concentration of efforts for the implementation of meaningful working practices with genres in the classroom, there is still a noticeable hiatus between what is learned by the Portuguese Language teachers during their initial formation and their teaching practice in Primary and Middle School. From this finding we established the objective of this work: it consists in analyze the treatment given to genre theories in the programs of graduation in Letters (Portuguese Language teaching courses) in the Colleges for teachers formation. This is a qualitative research based on the theorical contributions of Marcuschi (2008), Bakhtin ([1979] 2003), Bronckart (1999, 2006), Schneuwly e Dolz (2004), Machado (2009), Bazerman (2006a, 2006b, 2007), Miller (2009) among others, focused on questions addressed to the teaching work with genres in the context on Socio-Discursive Interacionism. This perspective suggests a new configuration for the Portuguese classes and a change of posture from the school in relation to the language teaching. In order to know better the reality around the role executed by the College in teachers formation with a profile which attends this new posture to be assumed by the school. This research was done through the analysis of the programs for the course of Letters, questionaries answered by the six participant teachers and observations done in the classrooms where each one of the participants teach. It was observed that the developed work with genres in the Colleges does not present a coherent position towards the presented discipline programs of the teaching institution, some of the teachers planning and the observed classroom experiences. The results still show that the work with genres can be much more connected to the individual pedagogical doing of each one of the participants then to the possible indications presented in the documents which organize and guide the teachers formation, even to that the own teacher announces in the questionaries they answerd and in their planning. Concerning to the developed activities by the teachers and their relation with the theorical assumptions defended here, it was evidenced the public institution whose theorical and metodologic approaches shows up a work under the light of the Socio- Discursive Interacionism for the treatment of genres in the initial formation of the Portuguese Language teachers